Baseline Psychological Treatment Reduces the Effect of Coaching in a Randomised Trial of a Depression Self-Care Intervention. (January 2017) - McCusker, Jane; Cole, Martin; Lambert, Sylvie; Yaffe, Mark; Ciampi, Antonio; Belzile, Eric
Objective: To explore the effects of baseline psychological and antidepressant medication treatment in a trial of lay telephone coaching in a low-intensity, supported depression self-care intervention. Method: A single blind, individually randomised, pragmatic trial was conducted among primary care adults with chronic physical conditions and comorbid depressive symptoms. Eligible subjects were randomised to receive a depression self-care toolkit with (intervention group) or without (control group) telephone coaching provided by trained lay coaches. For this brief communication, a secondary analysis of the trial data focused on the effects of baseline psychological and antidepressant treatments on mental health outcomes (Patient Health Questionnaire 9 [PHQ-9], SF-12 Mental Component Summary [MCS], Generalized Anxiety Disorder 7 [GAD-7]) and satisfaction with the intervention. Results: In total, 223 patients were randomised, and 165 (74.0%) completed both 3- and 6-month follow-ups. There were 2 significant interactions of baseline treatment and study group for 6-month mental health outcomes. A significant benefit of coaching on 6-month PHQ-9 was seen only among participants who were not receiving baseline psychological treatment. A smaller interaction was found for baseline antidepressant medications and 6-month mental health. There was a significant main effect for baseline psychological treatment and lower 6-month satisfaction. Conclusions: Depressed patients receiving baseline psychological treatment may not benefit from lay coaching offered as part of a low-intensity depression self-care intervention.